Correct Me If You Can - Optimal Non-Linear Taxation of Internalities - Andreas Gerster; Michael Kramm (Center for Economic Studies and ifo Institute (CESifo), 2019)
A growing literature has shown that behavioral biases influence consumer choices. Such so-called internalities are ubiquitous in many settings, including energy efficiency investments and the consumption of sin goods, such as cigarettes and sugar. In this paper, we use a mechanism design approach to characterize the optimal non-linear tax (or subsidy) for correcting behaviorally biased consumers. We demonstrate that market choices are informative about consumers' bias, which can be exploited for benevolent price discrimination via a non-linear tax schedule. We derive that such “internality revelation” depends on two sufficient statistics: the correlation between valuations and biases, as well as the signal-to-noise ratio of the bias. Furthermore, we find that there must be a minimum alignment of preferences among the designer and the consumer to ensure internality tax implementability. We contrast our results with the insights from standard non-linear income taxation and discuss that the optimal corrective tax schedule is typically convex. In addition, we apply our findings to the light bulb market and determine the optimal non-linear subsidy for energy efficiency.
Keywords: H21; D82; D04; Q58; 330; optimal commodity taxation; non-linear taxation; behavioral economics; public economics; internalities; environmental economics